ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR TEKS DESKRIPSI BERMUATAN LITERASI EMOSI DI SEKOLAH DASAR - Akmal Rizki Wiguna; Seni Apriliya (STKIP Subang, 2026)
ABSTRACT This study aims to analyze the need for developing descriptive text teaching materials integrated with emotional literacy in elementary schools. The research was motivated by the gap between the ideal learning process that integrates cognitive and affective aspects and the actual classroom practice, which still focuses primarily on conceptual understanding. This study employed a qualitative descriptive approach conducted at SDN 2 Gununglipung, involving one fifth-grade teacher and two students as research subjects. Data were collected through observation, interviews, and document analysis, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the existing descriptive text teaching materials are still print based and emphasize structural and conceptual elements without explicitly integrating emotional literacy components. Furthermore, students’ emotional literacy skills such as recognizing, naming, managing, and repairing emotions have not developed optimally. Both teacher and student perspectives reveal the need for more integrative, visually engaging, and digitally supported teaching materials. Therefore, the development of descriptive text teaching materials integrated with emotional literacy is considered necessary to support holistic learning that balances cognitive and affective development in elementary education.